The relation between hemoglobin and recurrent oral ulcer - Mustafa Al-Ahmad, Basma Ezzat; Kashmola, Muhanad Ali Hamdon; Mustafa, Nazih Shaban; Aziz, Abu Zarrin; Ismail, Amalina; AlAni, Imad Matloub Dally; Abdul Jabbar, Omar (2015)
Background / Objective:. The relation between Recurrent oral ulcer (ROU) and Hb is still controversial; a number of studies suggested that Hb deficiency may play a role in the pathogenesis of ROU. While conversely, these ulcerations typically are found identical clinically and histopathologically to those noted in otherwise healthy individuals.The aim of this study is to discover the relationship between RAU with hemoglobin level . Materials and method: this research is a cross-sectional study comprises of fifty patients presented with recurrent oral ulcers referred to oral medicine clinic, haemoglobin level was measured by using haemoglobinometer; (Hemocue Hb 201+). Results/ Discussion : According to our study, most of the patients with recurrent oral ulcerations have significantly low haemoglobin level (P < 0.001). The present study has demonstrated that patients with ROU tend to have low hemoglobin level compared to control group, 19 out of 23 male patients and 21 out of 24 female patients had significantly lower hemoglobin level p<0.001 The Mean values of hemoglobin and levels of control group were 13.5 mg/dL in males and 11mg/dL in females, whereas those of ROU group were 12.05± 0.8 mg/dL and 10.05.±1.06 mg/dL respectively Conclusion: This study shows high relation between recurrent oral ulceration and haemoglobin level. However, for further studies full haematologic investigations, longitudinal studies of large groups and long-term observation are required.